Comprehensive analysis of the LHT gene family in tobacco and functional characterization of NtLHT22 involvement in amino acids homeostasis - Li, Zhaowu; Gao, Junping; Wang, Shuaibin; Xie, Xiaodong; Wang, Zhangying; Peng, Yu; Yang, Xiaonian; Pu, Wenxuan; Wang, Yaofu; Fan, Xiaorong (Frontiers in Plant Science, 2022)
Amino acids are vital nitrogen (N) sources for plant growth and yield. The uptake and translocation of amino acids are mediated by amino acid transporters (AATs). The AATs family including proline transporters (ProTs), amino acid permeases (AAPs) and lysine-histidine transporters (LHTs) subfamilies have been identified in various plants. Nevertheless, little is known about these genes in tobacco. In this study, we identified 23 LHT genes, the important members of AATs, in the tobacco genome. The gene structure, phylogenetic tree, transmembrane helices, chromosomal distribution and evolution, promoter cis-elements, and expression profiles of NtLHT genes were systematically analyzed. Phylogenetic analysis divided the 23 NtLHT genes into two conserved subgroups. Expression profiles confirmed that the NtLHT genes were differentially expressed in various tissues, signifying their potential roles in tobacco growth and development. The results from cis-elements analysis of promoters and expression after stress treatments suggested that NtLHT genes might be involved in abiotic stress responses of tobacco. In addition, overexpression of NtLHT22 changed the amino acids homeostasis in the transgenic plants. The results from this study provide useful information for further in-depth studies on the molecular functions of the NtLHT genes.